Factor influencing agriculture`s contribution to GDP in Malaysia / Fareha Nazwa Watinin - Watinin, Fareha Nazwa (2020)
This study aims to determine the macroeconomic factor which influence the agriculture’s contribution to GDP in Malaysia. This study employs time series data for 30-year period spanning from 1989 until 2019. It was hypothesized that the percentage contribution of agriculture to GDP is influenced by factors associated with the level of economic development in Malaysia which is the government expenditure on agriculture, the inflation rate and net exports of agriculture. The result of the hypothesis shows that government expenditure to agriculture, inflation rate and net export of agriculture have a positive relationship with the agriculture contribution to GDP